Development of Mathematical Multiplication Board Game Media to Improve the Arithmetic Ability of 3rd Grade Elementary School Students - Wardani, Aprilia Budi; Hidayah , Wiranti Nur; Maharani , Tarisha Zetha; Rozi, Fahrur; Ellianawati, Ellianawati (Universitas Sarjanawiyata Tamansiswa, 2025)
Mastery of multiplication is essential for third-grade students, yet learning often remains limited to memorization, resulting in low numeracy skills. This study aims to develop a Multiplication Board Game as an interactive learning medium to strengthen students’ conceptual and operational understanding of multiplication. Using the ADDIE-based Research and Development (R&D) method, the product was validated by material, media, and instructional design experts, and tested on 19 third-grade students at Kataan Elementary School. Expert validation results showed a feasibility score of 87% (very feasible). The use of this media also improved student learning outcomes, increasing the average score from 62.11 (pre-test) to 81.05 (post-test). Student and teacher responses were in the “very good” category, indicating that the media is engaging, easy to use, and supportive of active learning. Theoretically, the media reinforces constructivist principles by providing concrete, visual, and interactive learning experiences aligned with students’ developmental stages. Practically, the Multiplication Board Game offers teachers an effective alternative to enrich mathematics instruction and enhance students’ numeracy performance.